The Contribution of Circular Economy Practices, Waste Management Literacy, and Infrastructure Support to the Sustainability of Urban Waste Management in Surabaya City - Farida Arinie Soelistianto; Rival Pahrijal; Rani Eka Arini (Westscience Press, 2026)
Urban waste management has become a critical challenge in rapidly growing cities due to increasing population, urbanization, and consumption patterns that generate large volumes of waste. Sustainable waste management systems are therefore required to reduce environmental impacts and improve resource efficiency. This study aims to analyze the contribution of circular economy practices, waste management literacy, and infrastructure support to the sustainability of urban waste management in the City of Surabaya. The research employs a quantitative approach using a survey method. Data were collected from 150 respondents through a structured questionnaire measured using a five-point Likert scale. The collected data were analyzed using SPSS version 25, including descriptive statistics, validity and reliability testing, and multiple linear regression analysis. The results of the study indicate that circular economy practices, waste management literacy, and infrastructure support all have positive and significant effects on the sustainability of urban waste management. Waste management literacy shows the strongest influence on sustainability, followed by circular economy practices and infrastructure support. The regression analysis shows that the three independent variables collectively explain 54.9% of the variation in urban waste management sustainability. These findings suggest that improving public environmental knowledge, encouraging circular economy practices such as recycling and waste reduction, and strengthening waste management infrastructure can significantly enhance sustainable urban waste management. The study provides practical implications for policymakers and urban planners to develop integrated strategies that combine community participation, environmental education, and infrastructure development to achieve sustainable waste management systems.